2022
DOI: 10.1101/2022.12.30.22284056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mood symptoms and chronic fatigue syndrome due to relapsing remitting multiple sclerosis are associated with immune activation and aberrations in the erythron

Abstract: Background: Multiple sclerosis (MS) is a chronic autoimmune and neuroinflammatory disease of the central nervous system characterized by peripheral activation of immune-inflammatory pathways which culminate in neurotoxicity causing demyelination of central neurons. Nonetheless, the pathophysiology of relapsing-remitting MS (RRMS)-related chronic fatigue, depression, anxiety, cognitive impairments, and autonomic disturbances is not well understood. Objectives: The current study aims to delineate whether the rem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 97 publications
(79 reference statements)
1
4
0
Order By: Relevance
“…A factor extracted from physical and emotional maltreatment and neglect as well as family problems had a substantial, significant direct effect on the phenome, according to this analysis. These results build upon the conclusions drawn by Almulla et al, 22 which indicated that ACEs could predict the phenome of depression. Consistent with previous research (e.g., Hein et al; 50 Peckins et al; 51 Gizdic et al 52 ), our findings demonstrate that distinct subtypes of ACEs are associated with psychopathology in unique ways.…”
Section: Effects Of Aces On the Depression Phenomesupporting
confidence: 88%
See 3 more Smart Citations
“…A factor extracted from physical and emotional maltreatment and neglect as well as family problems had a substantial, significant direct effect on the phenome, according to this analysis. These results build upon the conclusions drawn by Almulla et al, 22 which indicated that ACEs could predict the phenome of depression. Consistent with previous research (e.g., Hein et al; 50 Peckins et al; 51 Gizdic et al 52 ), our findings demonstrate that distinct subtypes of ACEs are associated with psychopathology in unique ways.…”
Section: Effects Of Aces On the Depression Phenomesupporting
confidence: 88%
“…23,24,73 Furthermore, increased NLEs were found to partially mediate the effects of ACEs on rumination, SB, neuroticism, and the phenome of depression, according to the current study. Almulla et al 22 discovered that NLEs combined with ACEs substantially predict the manifestation of very severe MDD, as well as the lifetime and current suicidal behaviors. These results build upon those of Almulla et al 22 The effects of ACEs on the increases in affective symptoms during the COVID -19 pandemic are partially mediated by increased NLE scores.…”
Section: Combined Effects Of Aces and Nles On The Phenome Of Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cytokines and chemokines belonging to the neurotoxicity profile all show a potential to damage the function or structure of neuronal cells or affect neuroplasticity or neurogenesis (Maes and Carvalho 2018, Almulla, Abbas Abo Algon et al 2023, Almulla, Abdul Jaleel et al 2023, Sreenivas, Maes et al 2024.…”
Section: Introductionmentioning
confidence: 99%